Low temperature synthesis and characterization of BiNbO4 powders - Radha, R.; Muthurajan, H.; Rao, N. Koteswara; Pradhan, Sivaram; Gupta, U. N.; Jha, Ratnesh Kumar; Mirji, S. A.; Ravi, V. (Materials Characterization, 2008)
BiNbO4 powders, a potential microwave dielectric ceramic were prepared by both coprecipitation and solid state techniques. In the former method, an aqueous ammonium hydroxide was used to precipitate Bi3+ and Ta5+ cations as hydroxides simultaneously under basic conditions. It is observed that the co-precipitation produces BiNbO4 phase on heating at 600 degrees C, whereas complete phase formation occurs only at 800 degrees C in the case of solid state method. The phase contents and lattice parameters were studied by powder X-ray diffraction. The sequence of the reaction and phase evolution of BiNbO4 were also studied by the X-ray diffraction. The samples were characterized by the differential-thermal/thermo-gravimetric analyses and scanning electron microscopy techniques. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: BiNbO4; Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Low temperature synthesis of SrNb2O6 and SrTa2O6 using hydroxide precursor - Muthurajan, H.; Kumar, H. H.; Koteswara Rao, N.; Pradhan, Sivaram; Jha, Ratnesh Kumar; Ravi, V. (Materials Letters, 2008)
SrNb2O6 (SN) or SrTA(2)O(6) (ST) compounds were prepared at low temperatures for the first time from hydroxide precursors. A simple procedure of mixing commercially purchased strontium hydroxide and niobium (or tantalum) hydroxide thoroughly together and heating at a low temperature (<400 degrees C) produced SrNb2O6 (SN) or SrTa2O6 (ST) powders. This is the lowest temperature so far reported for the formation of these phases. These materials are potential candidates for ferroelectric and electro-optic applications. The reaction sequence and evolution of the phase formation were investigated by X-ray diffraction (XRD) studies. The average particle size and morphology of these powders were studied by scanning electron microscopy (SEM). (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Electron microscopy; electronic materials; X-ray diffraction